Marketing Strategy Of Micro Small And Medium Business "Fantobiz" Banana Chips Through Digital Marketing And Improvement Of Product Identity During Covid-19 - Nadia Pitra Kinasih; Nurul Dwi Novikarumsari (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
The student study service program or KKN BTV III was held during covid-19 pandemic. This program hoped that students will still have the urgency of service so that they can develop their ability to socialize in the community by implementing health protocols and as a medium for business development for communities affected by Covid-19. KKN BTV III University of Jember is a KKN that has various themes or is called Thematic KKN. However, the theme taken by one of students is empowering entrepreneurs affected by COVID-19. Which is where the target of the BTV III KKN Student activity is the Banana Chips SMEs "Fantobiz". The work program he made was regarding the improvement of the identity branding sticker of an MSME and also market expansion by utilizing digital marketing in the form of Instagram, WhatsApp and Shopee as a medium for buying and selling Banana Chips Products online which aims to expand the sales range of "Fantobiz" banana chips to make it more affordable. famous to go out of town to increase sales. KKN BTV III students at the University of Jember not only help create digital marketing accounts but also train the use of digital marketing so that their businesses can then run on the provisions already owned by the MSMEs. And also the identity of the product is improved not only through the product sticker but also the making of a banner that becomes a flashlight for an MSME. Keywords: the student study service, MSMEs, Digital Marketing, Identity